Лексичні та граматичні риси мови грамот ХІV–ХV століть - Христенюк, Віра; Hristenok, Vera (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті проаналізовано лексичні та граматичні особливості українських ділових документів, зокрема грамот різних типів ХІV–ХV століть. Описанотематичні групи лексики, розглянуто слова й словотвірні варіанти, які за значенням і формою відрізняються від сучасних. Простежено процеси формування у студентів-філологів історичної пам’яті, позитивного мнемонічного простору, відтворення ментальної історії України під час опрацювання текстів документів.The article was devoted to analysis of lexical and grammatical features of Ukrainian business documents, including letters of different types of the XIV and XV centuries. It is established that the texts of letters designed in the style business using the vocabulary of home and work life. Described the thematic group of lexicon words and considered word formation variants that differ in meaning and form of the modern ones. We characterized the local dialect features charters, which are especially spelling Ukrainian literary language of this period, denotes the value of language literacy in the development and establishment of norms of the Ukrainian language. In addition, traces the process of the formation of students-philologists of historical memory, the positive mnemonic space, reproduce the mental history of Ukraine during word processing documents.
Lexical and Grammatical Features of Language Literacy XIV–XV Centuries
Keywords: діловий документ; староукраїнська мова; український правопис; діалектизм; історична пам’ять; business document; old Ukrainian language; Ukrainian spelling; dialecticism; historical memory